Challenges in simulating beam dynamics of dielectric laser acceleration - Niedermayer, Uwe; Adelmann, Andreas; Bettoni, Simona; Calvi, Marco; Dehler, Micha; Ferrari, Eugenio; Frei, Franziska; Hauenstein, Dominique; Hermann, Benedikt; Hiller, Nicole; Ischebeck, Rasmus; Lombosi, Csaba; et al. (International Journal of Modern Physics A, 2019)
Dielectric Laser Acceleration (DLA) achieves the highest gradients among structure-based electron accelerators. The use of dielectrics increases the breakdown field limit, and thus the achievable gradient, by a factor of at least 10 in comparison to metals. Experimental demonstrations of DLA in 2013 led to the Accelerator on a Chip International Program (ACHIP), funded by the Gordon and Betty Moore Foundation. In ACHIP, our main goal is to build an accelerator on a silicon chip, which can accelerate electrons from below 100 keV to above 1 MeV with a gradient of at least 100 MeV/m. For stable acceleration on the chip, magnet-only focusing techniques are insufficient to compensate the strong acceleration defocusing. Thus, spatial harmonic and Alternating Phase Focusing (APF) laser-based focusing techniques have been developed. We have also developed the simplified symplectic tracking code DLAtrack6D, which makes use of the periodicity and applies only one kick per DLA cell, which is calculated by the Fourier coefficient of the synchronous spatial harmonic. Due to coupling, the Fourier coefficients of neighboring cells are not entirely independent and a field flatness optimization (similarly as in multi-cell cavities) needs to be performed. The simulation of the entire accelerator on a chip by a Particle In Cell (PIC) code is possible, but impractical for optimization purposes. Finally, we have also outlined the treatment of wake field effects in attosecond bunches in the grating within DLAtrack6D, where the wake function is computed by an external solver.
Keywords: Dielectric; laser; accelerator; chip; ACHIP

Electron phase-space control in photonic chip-based particle acceleration - Kraus, Stefanie; Shiloh, Roy; Illmer, Johannes; Chlouba, Tomas; Yousefi, Peyman; Schönenberger, Norbert; Niedermayer, U.; Mittelbach, Anna; Hommelhoff, Peter (Optics InfoBase Conference Papers, 2022)
We demonstrate complex electron phase-space control in a 77.7 micrometer long silicon-based nanostructure. This low-loss electron transport scheme is a prerequisite to the future mega-electron-volt electron accelerator on a photonic chip.
CRIS-Team Scopus Importer:2022-09-09
Keywords: electron; phase-space control; photonic electron acceleration

Electron phase-space control in photonic chip-based particle acceleration - Shiloh, Roy; Illmer, Johannes; Chlouba, Tomas; Yousefi, Peyman; Schonenberger, N.; Niedermayer, U.; Mittelbach, Anna; Hommelhoff, Peter (Nature, 2021)
Particle accelerators are essential tools in science, hospitals and industry1–6. Yet their costs and large footprint, ranging in length from metres to several kilometres, limit their use. The recently demonstrated nanophotonics-based acceleration of charged particles can reduce the cost and size of these accelerators by orders of magnitude7–9. In this approach, a carefully designed nanostructure transfers energy from laser light to the particles in a phase-synchronous manner, accelerating them. To accelerate particles to the megaelectronvolt range and beyond, with minimal particle loss10,11, the particle beam needs to be confined over extended distances, but the necessary control of the electron beam’s phase space has been elusive. Here we demonstrate complex electron phase-space control at optical frequencies in the 225-nanometre narrow channel of a silicon-based photonic nanostructure that is 77.7 micrometres long. In particular, we experimentally show alternating phase focusing10–13, a particle propagation scheme for minimal-loss transport that could, in principle, be arbitrarily long. We expect this work to enable megaelectronvolt electron-beam generation on a photonic chip, with potential for applications in radiotherapy and compact light sources9, and other forms of electron phase-space control resulting in narrow energy or zeptosecond-bunched beams14–16.
CRIS-Team Scopus Importer:2021-10-01

From strong-field physics in and at nanoscale matter to photonics-based laser accelerators - Kozak, Martin; Higuchi, Takuya; McNeur, Joshua; Shiloh, Roy; Heide, Christian; Paschen, Timo; Yousefi, Peyman; Sturm, Constanze; Li, Ang; Illmer, Johannes; Meier, Stefan; Schönenberger, Norbert; et al. (205, 2019)
New ways of controlling quasi-free and free electrons by means of phase-controlled ultrashort laser pulses are demonstrated: from strong-field physics in the conducting 2-d material graphene and at the surface of nanostructures, to laser acceleration of free electrons with a nanophotonic structure, and the demonstration of the longitudinal Kapitza-Dirac effec

Generation and Characterization of Attosecond Microbunched Electron Pulse Trains via Dielectric Laser Acceleration - Schönenberger, Norbert; Mittelbach, Anna; Yousefi, Peyman; McNeur, Joshua; Niedermayer, Uwe; Hommelhoff, Peter (Physical Review Letters, 2019)
Dielectric laser acceleration is a versatile scheme to accelerate and control electrons with the help of femtosecond laser pulses in nanophotonic structures. We demonstrate here the generation of a train of electron pulses with individual pulse durations as short as 270±80 attoseconds(FWHM), measured in an indirect fashion, based on two subsequent dielectric laser interaction regions connected by a free-space electron drift section, all on a single photonic chip. In the first interaction region (the modulator), an energy modulation is imprinted on the electron pulse. During free propagation, this energy modulation evolves into a charge density modulation, which we probe in the second interaction region (the analyzer). These results will lead to new ways of probing ultrafast dynamics in matter and are essential for future laser-based particle accelerators on a photonic chip.

Towards a fully integrated accelerator on a chip: Dielectric Laser Acceleration (DLA) from the source to relativistic electrons - Wootton, K. P.; England, R. J.; Tantawi, S.; Aßmann, R. W.; Hartl, I.; Kärtner, F. X.; Kuropka, W.; Mayet, F.; Ruehl, A.; Rivkin, L.; Hommelhoff, Peter; Illmer, Johannes; et al. (IPAC 2017 - Proceedings of the 8th International Particle Accelerator Conference, 2017)
Dielectric laser acceleration of electrons has recently been demonstrated with significantly higher accelerating gradients than other structure-based linear accelerators. Towards the development of an integrated 1 MeV electron accelerator based on dielectric laser accelerator technologies, development in several relevant technologies is needed. In this work, recent developments on electron sources, bunching, accelerating, focussing, deflecting and laser coupling structures are reported. With an eye to the near future, components required for a 1 MeV kinetic energy tabletop accelerator producing sub-femtosecond electron bunches are outlined.
CRIS-Team Scopus Importer:2022-06-05

Ultrafast Electron Phase-space Control in a Nanophotonic Structure - Chlouba, Tomas; Shiloh, Roy; Illmer, Johannes; Kraus, Stefanie; Yousefi, Peyman; Schönenberger, Norbert; Niedermayer, U.; Mittelbach, Anna; Hommelhoff, Peter (Optics InfoBase Conference Papers, 2022)
We demonstrate ultrafast electron beam phase space control in a silicon-based nanostructure. With this we guide the electron beam through a 225 nm wide and 77 μm channel. This scheme can be applied in chip-based nanophotonic accelerators.
CRIS-Team Scopus Importer:2023-03-07